A new double ш-shaped compact negative refractive index metamaterial for wideband applications - Pujan Chandra Paul; Mohammad Jakir Hossain; Ashish Kumar Karmaker; Md. Jakirul Islam (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper analyzed the new compact design and negative refractive index (NRI) metamaterial for wideband applications. The proposed metamaterial exhibits NRI and wideband characteristics of the x-axis wave propagation. It displayed the NRI property at the frequency of 1.54 GHz and wideband from 1.26 GHz to 7.08 GHz frequency (L, S, and C band). Moreover, the response of the 1×2 horizontal and 2×1 vertical array structure showed the wideband frequency in the 7.17 GHz to 13.62 GHz and 1.46 GHz to 9.53 GHz, respectively. Electromagnetic simulation software called CST has been used to design the metamaterial unit cell. The metamaterial has been displayed the multi-band characteristics such as L, S, C, X and Ku bands with negative index material properties.